A Single Nonblinking Cs4PbBr6 Nanoparticle as a Nanothermometer. Issue 3 (4th February 2019) - Lei, Yanyu; Yang, Jie; Hong, Daocheng; Wan, Sushu; Hua, Yan; Xie, Mingcai; Tang, Xiaosheng; Tian, Yuxi
Abstract: Inorganic perovskite materials have attracted broad interest in the last several years due to their stability and promising applications as photovoltaic and light‐emitting materials. In this work, we prepared Cs4 PbBr6 nanoparticles showing stable photoluminescence (PL) without blinking and studied the PL properties of individual Cs4 PbBr6 nanoparticles in the biological temperature range. We found that both PL intensity and lifetime of a single Cs4 PbBr6 particle strongly depends on the temperature. The PL intensity and lifetime decrease almost linearly with the increasing of the temperature. The slopes of the PL intensity and lifetime versus temperature were as high as 2% and 3% per degree centigrade, respectively. The photostability and thermal stability were also checked for individual particles. With these results, we proposed that the sensitivity of PL intensity and lifetime of a single Cs4 PbBr6 nanoparticle on temperature showed the potential application of a single particle as a nanothermometer for thermal detection in a local environment. Abstract : Take the temperature : Non‐blinking Cs4 PbBr6 nanoparticles show potential as a single‐particle thermometers to detect local temperatures on the nanometer scale.